Creative teaching practices among islamic education lecturers in polytechnic - Norfarahi Zulkifli,; Mohd Isa Hamzah,; Khadijah Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2021)
In the reforms of the country's education landscape, the aspect of creativity is the focus in the Malaysian Education Development Plan (PPPM) 2013-2025 which aims to produce a creative and innovative workforce. It can be seen that education is the mainstay to nurture and enhance creativity among students which is the country’s main source of human capital especially in the institutions of higher learning. It is also inevitably a priority for a responsible teacher to move in line with the development of education and to improve teaching to be more creative. Elements of creativity in teaching and learning have been explored by researchers, but creativity among lecturers spesifically Islamic Education Lecturers have not been precisely discovered in previous study. Accordingly, this survey study was conducted to identify the level of creative teaching practices among polytechnic Islamic Education lecturers in Central and Southern Zone. The questionnaire was administered online and a total of 74 respondents were involved in this study and data collected were analysed using descriptive analysis of frequency, percentage and mean to report the findings. The findings of the study show that the level of creative teaching practice among polytechnic Islamic Education lecturers in Central and Southern is at a high level and it is hope that they can be more creative in order to achieve teaching and learning outcomes and at the same time develop students' creativity especially among the technical students in polytechnic.